ANALISIS DAMPAK PENGELOLAAN DANA DESA TERADAP PEMBERDAYAAN MASYARAKAT DI KECAMATAN MAGETAN KABUPATEN MAGETAN - Wulan Agustiningrum; Isharijadi Isharijadi; Liana Vivin Wihartanti (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2020)
This research is related to the management of Village Funds in Magetan District, Magetan Regency which focuses on the impact of Village Fund management on community empowerment. This study aims to examine the management of Village Funds and how it impacts in the field of community empowerment in Magetan District, Magetan Regency, fiscal year 2019. The type of research used is qualitative with a descriptive approach. The results of this study show that the management of the Village Fund in the 2019 fiscal year is managed in accordance with applicable regulations. The impact of the Village Fund on community empowerment is that it has a "positive" impact, where the absorption of the Village Fund realization reaches an average of 77% to 100%. In Magetan District, Magetan Regency, the use of Village Funds is prioritized for the development sector and the community empowerment sector. However, the use of the Village Fund for community empowerment only reaches 10% of its total revenue, in which the Village Fund focuses more on the development of infrastructure facilities and infrastructure.Keywords: Empowerment; Public; Village Fund